Development of a microbe domestication pod (MD Pod) for in situ cultivation of micro‐encapsulated marine bacteria. Issue 3 (3rd December 2020) - Alkayyali, Tartela; Pope, Emily; Wheatley, Sydney K.; Cartmell, Christopher; Haltli, Bradley; Kerr, Russell G.; Ahmadi, Ali
Abstract: Microbial marine natural products hold significant potential for the discovery of new bioactive therapeutics such as antibiotics. Unfortunately, this discovery is hindered by the inability to culture the majority of microbes using traditional laboratory approaches. While many new methods have been developed to increase cultivability, a high‐throughput in situ incubation chamber capable of simultaneously isolating individual microbes while allowing cellular communication has not previously been reported. Development of such a device would expedite the discovery of new microbial taxa and, thus, facilitate access to their associated natural products. In this study, this concept is achieved by the development of a new device termed by the authors as the microbe domestication (MD) Pod. The MD Pod enables single‐cell cultivation by isolating marine bacterial cells in agarose microbeads produced using microfluidics, while allowing potential transmission of chemical signals between cells during in situ incubation in a chamber, or "Pod, " that is deployed in the environment. The design of the MD Pod was optimized to ensure the use of biocompatible materials, allow for simple assembly in a field setting, and maintain sterility throughout incubation. The encapsulation process was designed to ensure that the viability of marine sediment bacteria was not adversely impacted by the encapsulation process. The process was validated using representative bacteria isolated from temperate marine sediment samples: Marinomonas polaris, Psychrobacter aquimaris, and Bacillus licheniformis . The overall process appeared to promote metabolic activity of most representative species. Thus, microfluidic encapsulation of marine bacteria and subsequent in situ incubation in the MD Pod is expected to accelerate marine natural products discovery by increasing the cultivability of marine bacteria. Abstract : A high‐throughput in situ incubation chamber capable of simultaneously isolating individual microbes while allowing cellular communication is developed in this work in an aim to increase the cultivability of marine bacteria which hold potential for the discovery of new bioactive therapeutics. The chamber design was optimized to ensure the use of biocompatible materials, simple assembly in a field setting, and sterility throughout incubation, validated using representative bacteria isolated from temperate marine sediment samples: Marinomonas polaris, Psychrobacter aquimaris, and Bacillus licheniformis .